Quantifying the Impact of Wind‐Current Feedback on Mesoscale Variability in Forced Simulation Experiments of the Agulhas Current Using an Eddy‐Tracking Algorithm. Issue 1 (14th January 2020) - Braby, Laura; Backeberg, Björn; Krug, Marjolaine; Reason, Chris
Abstract: The variability in the source regions of the Agulhas Current is influenced by mesoscale eddies. While existing numerical models are successfully able to capture many aspects of the Agulhas Current, many models are unable to accurately represent the observed eddy dissipation and interaction processes, affecting our understanding of mesoscale variability within the current. In this study, we compare two forced simulation experiments in a regional Hybrid Coordinate Ocean Model (HYCOM), where we change the wind forcing, and using an eddy‐tracking algorithm quantify the local effect of the changed wind stress on source region eddies and their interaction with the northern Agulhas Current. There is an overall reduction in eddy kinetic energy (EKE) over the domain, and the representation of Agulhas Current velocities are improved. This study shows that the contribution of meanders and small eddies to the total EKE of the region is greater than the EKE contribution from tracked mesoscale eddies. Changes in eddy properties resulting from the change in forcing from absolute to relative winds (the wind speed relative to the current speed) have resulted in significantly different mesoscale eddy properties. Finally, the evolution of meanders in the Agulhas Current, including the frequency and dissipation of smaller meanders and Natal Pulse type meanders, was assessed using HYCOM experiments and compared to satellite observations. The simulated frequency of smaller meanders compares more favorably to the observations with the change in wind forcing. However, larger Agulhas Current meanders are now too infrequent in the regional HYCOM. Plain Language Summary: Variability in the Agulhas Current is influenced by eddies forming in the Mozambique Channel and south of Madagascar. Many numerical models are not able to accurately simulate the interaction of these eddies with the Agulhas Current. Recently, coupled ocean‐atmosphere models have shown that the inclusion of current feedback to the atmosphere has a damping effect on mesoscale eddies. Here we compare two forced Hybrid Coordinate Ocean Model (HYCOM) simulations to determine the effect of a change in wind forcing on source region eddies and their interaction with the northern Agulhas Current. The first simulation is forced with absolute winds, while the second simulation is forced with relative winds (the wind speed relative to the current speed). In this study we show that the representation of the Agulhas Current is improved with a relative wind forcing. There is a reduction in eddy kinetic energy over the domain, and it is demonstrated that beyond the large mesoscale eddies, other processes such as meanders, small eddies, and short‐lived eddies contribute extensively to the total eddy kinetic energy budget. The change in wind forcing in the regional HYCOM has reduced the strength of mesoscale eddies and also resulted in fewer Agulhas Current meanders. Key Points: A change in wind forcing in the Hybrid Coordinate Ocean Model improves the representation of Agulhas mean and eddy kinetic energies The contribution of meanders and small eddies to the total eddy kinetic energy is greater than the contribution from mesoscale eddies A reduction in source region eddy amplitudes and circum‐averaged speeds occurs with the inclusion of current feedback in the wind forcing